Legal Analysis of the Implementation of Article 1 of the World Declaration on Higher Education - Sarsembayev , M.A. (Bulletin of the Karaganda University “Law Series”, 2025)
This article attempts to examine the legal application of Article 1 of the World Declaration on Higher Education for the Twenty-First Century. Article 1 of the World Declaration is an introductory, general article that helps the reader and professionals in the educational and pedagogical, legal spheres to understand the entire document as a whole. This article generally describes approaches and methods in the educational sphere, through which it is possible to achieve training and preparation of highly qualified personnel. The paragraphs of Article 1 of the World Declaration establish general methods and approaches to organizing and conducting the educational process. The essence of the educational process at universities is linked with the scientific activity of both students and teachers, who can engage in science independently from each other, as well as together. Engagement in scientific activity contributes to the educational process in various forms and types. Science contributes to the student’s pursuit of higher education and shapes the students’ inclinations to fundamental and applied science, which become predetermining for the rest of their lives. Science and practice involved in the process of educational activities at the university allow students to become highquality professionals not only in the profession, but also in the ability in competent management.